To wake up every morning and see that life is okay...”: the everyday experiences of women who are grant recipients in South Africa - Maphelela, Koketso (My University, 2021)
In South Africa, social security grants are one way of redistributing the country’s wealth to the “legally” marginalized groups, the majority of whom are black people. Grants have been made available to improve the recipients’ precarious economic situations and reduce hunger in poverty-stricken homes. With democracy, there was hope that black people would be in a better social and financial standing. However, political liberation did not mean better opportunities for many, and South Africa’s democratization only saw a small percentage of black people escape the hands of poverty (Bahre, 2011). This research report addresses the caregivers’ experiences1 of the Child Support and Old Person’s grant recipients. It focuses very intimately on the participants’ personal lives while also drawing from my perspective of being raised by a woman who was a grant recipient herself, my grandmother. The question explored is “How have the caregivers of the grant recipients navigated their everyday lives, and how do they perceive their experiences?” There have been numerous nuanced outcomes from the interviews: grant recipients report being sustained by the grant funds while expressing that the funds cannot cover the beneficiaries’2 basic needs. Some participants said that they are entitled to the states’ funds, while others feel that the grants are given as a gift from the state. Furthermore, the research report argues that social support grants enter and circulate within existing and gendered networks of care and reciprocity. An analysis of their impact cannot solely focus on the beneficiaries when the rest of the family needs financial assistance. There needs to be more understanding of the recipient’s circumstances as income poverty is not the primary type of unfreedom recipients experience. I flesh out my argument in chapters that focus on; the network of the intergenerational relations that women have created, the entitlement that citizens have to these funds, and state violence.
A research project submitted in partial fulfilment of the requirements for the degree Master of Arts in Social Anthropology to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, 2021